Penentuan model kawasan potensi jenayah menggunakan proses hierarki analitik dan sistem maklumat geografi - Mohd. Shamsuddin, Nurul Hazwani (2013)
Increasing crime rates occurring in a community can be associated with several factors such as land use, economics, building use and demography. A preliminary survey was conducted and showed that land use and building use are the key contributors to crime. By determining the highest weight of value between land use and building use factors, the research seeks to develop a crime area model. The areas of crime studied and identified to reduce the crime rate comprised potential areas of crime in Dewan Bandaraya Kuala Lumpur (DBKL). Multi Criteria Decision Making (MCDM) method was used to determine the weight value of crime factors and each factor was found to have different weight values. The weight values of each factor were used in conventional MCDM but were not consistent and realistic. Thus, Analytical Hierarchy Process (AHP) method was used to produce more consistent and realistic weight values of crime factors by calculating the validation of the consistency ratio (CR). The weight values obtained from AHP for land use was 0.571 and was 0.429 for building use. These results showed that the CR values are below 0.1 and found to be consistent. Thus, these values as well as findings from previous AHP were applied to the Geographical Information System (GIS) to develop a potential crime areas model. The proposed model was visualized in spatial mapping and is capable of identifying potential crime areas classified as high, medium and low. The potential crime areas model would assist the authorities to identify and rank the crime areas accordingly